Pembuatan Akun Twitter, Instagram, dan Blog sebagai Media Promosi di Perpustakaan Universitas Dharma Andalas - Yuliana, Gina Erma; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed about the account creation twitter, instagram and Blogs as media promotion at Dharma Andalas University Library. The purpose of this paper is to determine the steps to create twitter, instagram and Blogs as media promotion at Dharma Andalas University Library. The method used in this paper is descriptive method. Data were collected through direct observation, interviews with the head of Dharma Andalas University Library and literature. Based on observations and interviews can be concluded that the Dharma Andalas University Library not do promotions through social media twitter, instagram and Blog. Based on the results, it can be concluded that social media twitter, instagram and Blogs can be used as promotional media library. As a promotional media library, the information displayed on the profile twitter, instagram and Blog is about the profile of the library. Such information is the name of the library, library addresses, opening hours of libraries and library slogan which is the hallmark of a library. Twitter and instagram Dharma Andalas University Library created to promote various activities to be and has been implemented by Dharma Andalas University library. Promotion via twitter and instagram to do with the upload photos and video with captions to describe an uploaded photo Blog Library Universias Dharma Andalas made to promote the library through activities that have already been made to write an article form a community in order to better introduce Dharma Andalas University Library to the public.Keyword: Promotion, Twitter, Instagram, Blog